2017
DOI: 10.1007/s11896-017-9227-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Group Performance in a Police Criminal Investigation Department: the Role of Gender Homogeneity, Leadership and Team Characteristics

Abstract: The Netherlands' Ministry of Security and Justice has agreed on performance targets with the country's police departments. Introducing the targets created a shift to controlling performance in team management focus. This empirical study of police teams in Utrecht in the Netherlands (N = 134) focuses on the influence of leadership style, gender and psychosocial team factors when teams are required to achieve agreed performance objectives. We address calls in the literature for more research into (objective) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This suggests that efforts will therefore need to be made to bridge what Rowe (2006) calls the credibility gap between frontline officers and these new police leaders. Research has identified a range of strategies that could be adopted to address these credibility issues including making junior officers feel more involved and valued in decision-making processes (Steinheider and Wuestewald 2008) or leaders actively creating organizational contexts that prevent an internal us versus them mentality developing between top management and other tiers within the police (Haake et al 2015;Schaveling et al 2017). …”
Section: Leadership In Policingmentioning
confidence: 99%
“…This suggests that efforts will therefore need to be made to bridge what Rowe (2006) calls the credibility gap between frontline officers and these new police leaders. Research has identified a range of strategies that could be adopted to address these credibility issues including making junior officers feel more involved and valued in decision-making processes (Steinheider and Wuestewald 2008) or leaders actively creating organizational contexts that prevent an internal us versus them mentality developing between top management and other tiers within the police (Haake et al 2015;Schaveling et al 2017). …”
Section: Leadership In Policingmentioning
confidence: 99%
“…EEG and communication data were analysed to understand entrainment between team members as they progressed through a task. Such analysis enables better task related performance evaluation that result from team-level entrainment, for example, in understanding leader driven theories [86,56,87] where speech from the leader induces motivation that affects team-processes eventually reflecting in enhanced performance [52]. Multimodal approaches have also been favoured in enhancing team training outcomes and assessments [52,36].…”
Section: Multimodality In the Context Of Teamsmentioning
confidence: 99%
“…Although these perspectives focused on the organizational landscape surrounding investigations as well as the challenges investigators face in their professional decision-making, there have also been calls to examine criminal investigation from the perspective of detectives’ social worlds (Innes, 2003), viewing police work as a social accomplishment with frequent intra- and interorganizational collaborations (see Manning, 1977; Schaveling et al, 2017; Tong and Bowling, 2006). Salet’s (2017) study of framing in temporary investigation teams employs such a perspective because the author showed how sensemaking and the establishment of consensus regarding various cases are largely related to interactions and social relations within the team.…”
Section: The Social Nature Of Detective Workmentioning
confidence: 99%